EXPERIMENTAL MODELS REGARDING THE BIOMECHANICS OF THE MASTICATORY SYSTEM - Raluca-Cristina Mocanu; Maria-Alexandra Martu; Irina-Georgeta Sufaru; Diana-Maria Anton; George-Alexandru Maftei; Ionut Luchian; Silvia Martu (Romanian Dental Association for Education, 2022)
Concerns about occlusal overload and the presumed consequences of occlusal trauma have led to meticulous replacement of missing teeth and the incorporation of a large number of supporting teeth into fixed dentures. For the experimental study of the state of tension and deformation that arises in the masticatory system during mastication, various methods are used, of which the most used in Romania are the methods that use resistive electrical tensometry, optical methods. Among the optical methods that provide the most commonly used qualitative and quantitative results are: the brittle varnish method and the holographic method. The obtained results are congruent with the results obtained by other researchers and through the conclusions drawn, the methodologies designed can be used for the experimental analysis of the state of tension and deformation in the masticatory system.